Efektivitas Biofumigan Dari Tanaman Sawi Putih Terhadap Nematoda Puru Akar (Meloidogyne spp.) Pada Tanaman Seledri - Nor Hapizah Ariani1; Dewi Fitriyanti; Muhammad Indar Pramudi Pramudi (JURNAL PROTEKSI TANAMAN TROPIKA, 2026)
Celery plant (Apium graveolens L.) is a leafy vegetable with various uses, such as adding flavor to food and having therapeutic qualities. In the Banjarbaru area, specifically in Sukamaju Village, many farmers cultivate celery, but there is a major obstacle to productivity, namely attacks by root knot nematodes (Meloidogyne spp.) causes root knot disease. This disease stunts the growth of celery plants, characterized by knots or nodules that appear in chains on the roots. Visible symptoms include yellowing of the celery leaves and stunted growth. Therefore, control measures are needed to suppress root knot disease. One control measure that can be implemented is the use of biofumigants, which utilize compounds likeGlucosinolates (GSL) and isothiocyanates (ITC) compounds found in plants from the Brassicae family, one of which is Chinese mustard greens. This study aims to determine how well Chinese cabbage plants reduce NPA in celery plants. The study used a single-factor Completely Randomized Design (CRD) method, with 500 eggs as the treatment. Meloidogyne spp. (control/T0) and 3 treatments with chopped Chinese cabbage, namely 500 eggs Meloidogyne spp. + 250 g of chopped white cabbage (T1) 500 eggs Meloidogyne spp. + 500 g of chopped white cabbage (T2) and 500 eggs Meloidogyne spp. + 750 g of chopped Chinese cabbage (T3). The results of this study indicate that celery plants with T2 treatment can suppress disease severity and the average number of NPA populations. The highest disease severity was found in T0 plants with a percentage of 5.23% and the lowest percentage in T2 treatment plants at 2.80%. The highest NPA population was also found in T0 plants at 448.25 and the lowest population in T2 plants at 117.25.